Optimalisasi Rantai Nilai Manggis : Strategi Penguatan Kelembagaan dan Daya Saing Ekspor di Kabupaten Banyuwangi - Nani Mardiyanti (Jurusan Ilmu Ekonomi Fakultas Ekonomi Universitas Trunojoyo Madura, 2026)
The horticultural sub-sector, particularly the mangosteen commodity, plays a strategic role as Indonesia's leading export commodity which requires integrated supply chain management. and globally competitive. The results of quantitative analysis using the SAW method, with high weighting on the criteria of Effectiveness and Feasibility, determine the priority order of policy interventions. six category identified root problems, Institutional Root Problems (Vi Score = 4.15) are at ranked first. Furthermore, the Upstream-Downstream Institutional Partnership Development strategy based on Cooperatives/Village-Owned Enterprises/Farmer Groups (Gapoktan) in mangosteen commodities was designated as Priority I with the highest preference value (V=0.93), making it an essential prerequisite for successful investment in this sector. The main objective is to transform cooperatives/Village-Owned Enterprises/Farmer Groups in production centers into Perpetrator Main Tata Commerce (Single) Mangosteen Exports that implement One Gate Policy. Implementation policy explained through three dimensions action: Regulation Mandate, which focuses on issuing Regional Head Regulations (Perkada) for legality; Governance, which includes facilitation Partnership Contract Long-term binding quality standards and minimum purchase prices; and synergy Program, which directs all funding support and technical programs of OPD through This policy emphasizes the centralization of authority and resources to create an integrated, competitive, and sustainable mangosteen export system. Keywords: Mangosteen, Banyuwangi, Partnership Upstream-Downstream